Shariah Screening Methodology: Does It ‘Really’ Shariah Compliance? - Abdullah Mohammed Ahmed Ayedh; Amir Shaharuddin; Muhammad Iqmal Hisham Kamaruddin (Ekonomi Syariah IAIN Kudus, 2019)
The Shariah financial screening indices is to exclude companies with unacceptable levels of conventional debt, liquidity, interest-based investment and/or impure income. Ideally, companies must not borrow on the basis of interest rate, nor invest in debt-bearing instruments, as well as not generating income through any other Shariah-impermissible activities. However, such restrictions would screen out the vast majority - if not all - of the stocks that are available on the market, even those listed in Islamic countries. Based on this condition, Shariah scholars tried to come out with a set of Shariah indices to be tested on existing companies in order to classify them as Shariah-compliant companies. Thus, the aim of this paper is to explore and critically analyse comparison of Shariah screening methodology amongst major Shariah indices in the world. By applying the reviewing for all related literature and contents of Shariah screening’s laws and regulations. It can be stated that several group of Shariah indices can be categorized. Firstly, under qualitative measures (business activities), there are two groups which are: (i) financial activities orientation; and (ii) indic with non-financial activities orientation. Meanwhile, under quantitative measures (financial ratios), another several groups can be categorized based on different adoption in the nominator, denominator and tolerate percentage used. It is hoped that this work would inspire more research on Shariah screening using different research methods and compare between the indices according to segments this research argued. Besides, the policy makers should give more attention to ensure the Shariah screening practices and the enhancement Shariah screening standardizing among the major Shariah indices. Last but not least, investors and stakeholders whom concern of Shariah screening could also benefited of the findings of this study by having better understanding of Shariah screening practices and compare between existed indices.